Metode Pendidikan Karakter di Pondok Pesantren Baitul Hikmah Tasikmalaya - Nurjanah, Nurjanah; Anwar Muhtadi, Dedi; Abdussalam, Agus (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Character education is critical given in any Islamic institution. At Boarding School Baitul Hikmah, character education in the broad sense is also very overlooked because of the strength of boarding, among other things that lie in student character education. In the Islamic world, characters always come first because they become the main base of human life, while science is second. Students studying in boarding school Baitul Hikmah must first be educated and depraved up substantially, and then they are given the knowledge that as many. Using the descriptive method, this study concluded that character education methods in Baitul Hikmah Islamic boarding schools are modeling, habituation, motivation, and discipline.